2010
DOI: 10.1002/mc.20688
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin disease risk: Role of genetic polymorphisms and gene–gene interactions in inflammation pathway genes

Abstract: Inflammation is a critical component of cancer development. The clinical and pathological features of Hodgkin disease (HD) reflect an abnormal immunity that results from cytokines secreted by Reed-Sternberg cells and the surrounding tumor. Numerous studies have reported the association between genetic polymorphisms in cytokine genes and the susceptibility to different hematologic cancers. However, the effects of such SNPs on modulating HD risk have not yet been investigated. We hypothesized that gene-gene inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 45 publications
2
22
0
Order By: Relevance
“…In our study, no association was observed between vaccine-induced immune responses and the presence of SNP rs3764880. The TLR7 SNP rs179008 has been associated with accelerated HIV-1 disease progression (33) and decreased risk for Hodgkin's disease (34). SNP rs179008 was detected in the 3 patients in Arm B who had detectable NY-ESO-1—specific CD8 + T-cell responses and in 1 patient in Arm A who did not have a detectable NY-ESO-1—specific CD8 + T-cell response (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, no association was observed between vaccine-induced immune responses and the presence of SNP rs3764880. The TLR7 SNP rs179008 has been associated with accelerated HIV-1 disease progression (33) and decreased risk for Hodgkin's disease (34). SNP rs179008 was detected in the 3 patients in Arm B who had detectable NY-ESO-1—specific CD8 + T-cell responses and in 1 patient in Arm A who did not have a detectable NY-ESO-1—specific CD8 + T-cell response (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, many studies have investigated the association between TLRs polymorphisms and cancer risk (Zhou et al, 2006;He et al, 2007;Purdue et al, 2009;Ng et al, 2010;Monroy et al, 2011), but the results were inconclusive. Different from the similar meta-analysis in Neoplasma (Wang et al, 2013), the Delta22 polymorphism (-196 to 174 del) was not analyzed in our manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the polymorphisms of these TLR genes in cancer etiology is almost completely unknown. However, there has been no association of the TLR3 polymorphisms with breast cancer (Etokebe et al [195]), cervical cancer (Pandey et al [197]), or HL (Monroy et al [201]). Similar results were obtained for nasopharyngeal carcinoma (He et al [202]), excluding the 829A/C polymorphism, heterozygous genotype, which correlates with increased risk of this malignancy.…”
Section: Tlr9 Genementioning
confidence: 97%
“…The rs3775290 polymorphism is not associated with the risk of either breast or cervical cancer and possibly is not important for oncogenomics. Polymorphisms of TLR5 and TLR8 genes do not correlate with altered lymphoma risk, but the rs179008 polymorphism of the TLR7 gene was associated with a lower risk of HL [201].…”
Section: Tlr9 Genementioning
confidence: 97%